2019
DOI: 10.1038/s41419-019-1848-y
|View full text |Cite
|
Sign up to set email alerts
|

The POU4F2/Brn-3b transcription factor is required for the hypertrophic response to angiotensin II in the heart

Abstract: Adult hearts respond to increased workload such as prolonged stress or injury, by undergoing hypertrophic growth. During this process, the early adaptive responses are important for maintaining cardiac output whereas at later stages, pathological responses such as cardiomyocyte apoptosis and fibrosis cause adverse remodelling, that can progress to heart failure. Yet the factors that control transition from adaptive responses to pathological remodelling in the heart are not well understood. Here we describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 65 publications
2
29
0
Order By: Relevance
“…Many observations that link the loss of Brn-3b with metabolic dysfunction and adverse cardiac responses to stress arise from studies using the global Brn-3b KO mice . However, these are strongly supported by additional data using either wild-type mice or in-vitro models [18][19][20]47 . For example, while the first evidence showing an association between a loss of Brn-3b and metabolic dysfunction (hyperglycaemia and insulin resistance) has been identified using constitutive Brn-3b KO mutants in vitro studies have confirmed that Brn-3b, is itself, regulated by key metabolites such as glucose, insulin and fatty acids, which are dysregulated in obesity and T2D 20 .…”
Section: Brn-3b: Linking Metabolic Dysfunction and Cvdmentioning
confidence: 88%
See 4 more Smart Citations
“…Many observations that link the loss of Brn-3b with metabolic dysfunction and adverse cardiac responses to stress arise from studies using the global Brn-3b KO mice . However, these are strongly supported by additional data using either wild-type mice or in-vitro models [18][19][20]47 . For example, while the first evidence showing an association between a loss of Brn-3b and metabolic dysfunction (hyperglycaemia and insulin resistance) has been identified using constitutive Brn-3b KO mutants in vitro studies have confirmed that Brn-3b, is itself, regulated by key metabolites such as glucose, insulin and fatty acids, which are dysregulated in obesity and T2D 20 .…”
Section: Brn-3b: Linking Metabolic Dysfunction and Cvdmentioning
confidence: 88%
“…Moreover, early studies using constitutive Brn-3b knockout (KO) mice revealed essential roles for Brn-3b in maintaining survival and specification of retinal ganglion cells (RGCs), since homozygous Brn-3b KO mutants are blind, due to loss of~70% of RGCs, postnatally 24,25,30,35 . More recent studies using these mutants have also highlighted essential and previously unknown roles for Brn-3b in regulating genes that control the fate and function of metabolic, vascular and cardiac cells 18,20 (see later).…”
Section: Brn-3b/pou4f2 Transcription Factor (Tf)mentioning
confidence: 97%
See 3 more Smart Citations